Proteasomal Degradation of Nod2 Protein Mediates Tolerance to Bacterial Cell Wall Components - Lee, Kyoung-Hee (American Society for Biochemistry and Molecular Biology, 2012)
The innate immune system serves as the first line of defense by detecting microbes and initiating inflammatory responses. Although both Toll-like receptor (TLR) and nucleotide binding domain and leucine-rich repeat (NLR) proteins are important for this process, their excessive activation is hazardous to hosts; thus, tight regulation is required. Endotoxin tolerance is refractory to repeated lipopolysaccharide (LPS) stimulation and serves as a host defense mechanism against septic shock caused by an excessive TLR4 response during Gram-negative bacterial infection. Gram-positive bacteria as well as their cell wall components also induce shock. However, the mechanism underlying tolerance is not understood. Here, we show that activation of Nod2 by its ligand, muramyl dipeptide (MDP) in the bacterial cell wall, induces rapid degradation of Nod2, which confers MDP tolerance in vitro and in vivo. Nod2 is constitutively associated with a chaperone protein, Hsp90, which is required for Nod2 stability and protects Nod2 from degradation. Upon MDP stimulation, Hsp90 rapidly dissociates from Nod2, which subsequently undergoes ubiquitination and proteasomal degradation. The SOCS-3 protein induced by Nod2 activation further facilitates this degradation process. Therefore, Nod2 protein stability is a key factor in determining responsiveness to MDP stimulation. This indicates that TLRs and NLRs induce a tolerant state through distinct molecular mechanisms that protect the host from septic shock.